SURG-28. ADULT MIDLINE GLIOMAS TREATED WITH LASER INTERSTITIAL THERMAL THERAPY (LITT): OUR COMPARATIVE EXPERIENCE WITH NEEDLE BIOPSY. (14th November 2022) - Merenzon, Martin; del Pont, Francisco Marcó; Morell, Alexis; Higgins, Dominique; Patel, Nitesh; Kader, Michael; Levy, Adam; Eatz, Tiffany; Eichberg, Daniel; Shah, Ashish; Silva, Michael; Luther, Evan; et al.
Abstract: INTRODUCTION: Adult midline gliomas are rare entities, with a scarcity of available clinical data. These patients have variable courses, with limited evidence to predict outcomes. Emerging evidence suggests that biomolecular profiles may play a significant role in outcomes, so tissue diagnosis is a key component of management. However, the role of cytoreductive therapy, such as Laser Interstitial Thermal Therapy (LITT) remains unknown. To date, only a few studies have described the use of MRI-guided LITT for managing midline gliomas. OBJECTIVE: To present a retrospective analysis of a single-center two-surgeon experience treating adult midline gliomas with either biopsy/LITT or biopsy alone. METHODS: Patients with midline intraxial tumors surgically treated at our tertiary care referral center were identified using our established database. Twenty-one patients managed either with biopsy/LITT or needle biopsy from 2015 to 2021 were included. Demographics and clinical records including, among others, length of hospital stay, preoperative lesion size, ablation volume, perioperative complications, adjuvant treatment, and stratified overall survival (OS) were collected. RESULTS: The two cohorts were composed of 7 patients who underwent LITT, and 14 biopsies. The mean age was 60.95y (25-82). The average tumor volumes were 16.99 cm 3 and 15.41 cm 3 for LITT and biopsy, respectively. No post-surgical complications were found in the LITT group, one patient had a postsurgical hemorrhage after biopsy. The mean OS was 20.28 ± 9.63 months in the LITT group, which was greater but not statistically significant than in the biopsy group (11.05 ± 4.45 months) (p = 0.605). CONCLUSION: Our results show that LITT is as safe as needle biopsy for the treatment of adult midline gliomas, and may offer a survival benefit given its cytoreductive properties.